Solitons and Their Biperiodic Pulsation in Ultrafast Fiber Lasers Based on CB/GO - Ju, Zhen-Tao; Si, Zhi-Zeng; Yan, Xin; Dai, Chao-Qing (Chinese physics letters, 2024)
The carbon black (CB) is introduced to manufacture CB/graphene oxide (GO) composite material to mitigate limitations of GO as a saturable absorber with the excellent performance in ultrafast fiber lasers. At a central wavelength of 1555.5 nm, the stable mode-locked pulse with width of 656 fs, repetition rate of 20.16 MHz, and high signal-to-noise ratio of 82.07 dB is experimentally obtained. Additionally, experimental observations for pulsation phenomena of vector biperiodic solitons combining period-1 and period-17, period-2 and period-32, period-3 and period-36 are verified via simulations.